2021
DOI: 10.5662/wjm.v11.i4.187
|View full text |Cite
|
Sign up to set email alerts
|

Evidence based review of management of cardiorenal syndrome type 1

Abstract: Cardiorenal syndrome (CRS) type 1 is the development of acute kidney injury in patients with acute decompensated heart failure. CRS often results in prolonged hospitalization, a higher rate of rehospitalization, high morbidity, and high mortality. The pathophysiology of CRS is complex and involves hemodynamic changes, neurohormonal activation, hypothalamic-pituitary stress reaction, inflammation, and infection. However, there is limited evidence or guideline in managing CRS type 1, and the established therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Cardiorenal syndrome (CRS) is highly prevalent in patients with ADHF and is associated with poor clinical outcomes [ 33 ]. Levosimendan increases renal blood flow through renal vasodilatation after cardiac surgery in hemodynamically stable patients with acute kidney injury (AKI) [ 34 ]. Early recognition and treatment of CRS can significantly improve the clinical outcomes of the patients [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiorenal syndrome (CRS) is highly prevalent in patients with ADHF and is associated with poor clinical outcomes [ 33 ]. Levosimendan increases renal blood flow through renal vasodilatation after cardiac surgery in hemodynamically stable patients with acute kidney injury (AKI) [ 34 ]. Early recognition and treatment of CRS can significantly improve the clinical outcomes of the patients [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent evidence-based review of the management of type 1 CRS concluded that the management of CRS type 1 is often challenging due to a variety of mechanisms leading to WRF and the lack of new treatment approaches targeting renal dysfunction in HF patients. UF appears to be complex and associated with high costs, so it is still not justified for CRS patients [ 74 ].…”
Section: Clinical Studiesmentioning
confidence: 99%
“… 1 CRS often is related to prolonged hospitalization, a greater likelihood of rehospitalization, worse morbidity, and increased mortality. 2 CRS is divided into five subtypes of which CRS type I (CRS1) is the most common. CRS1, also known as acute CRS, refers to acute worsening of heart function leading to kidney injury and/or dysfunction.…”
Section: Introductionmentioning
confidence: 99%